Boosting High-Voltage Practical Lithium Metal Batteries with Tailored Additives - You, Jinhai; Wang, Qiong; Wei, Runhong; Deng, Li; Hu, Yiyang; Niu, Li; Wang, Jingkai; Zheng, Xiaomei; Li, Junwei; Zhou, Yao; Li, Jun‑Tao (Nano-Micro Letters, 2024)
The lithium (Li) metal anode is widely regarded as an ideal anode material for high-energy-density batteries. However, uncontrolled Li dendrite growth often leads to unfavorable interfaces and low Coulombic efficiency (CE), limiting its broader application. Herein, an ether-based electrolyte (termed FGN-182) is formulated, exhibiting ultra-stable Li metal anodes through the incorporation of LiFSI and LiNO3 as dual salts. The synergistic effect of the dual salts facilitates the formation of a highly robust SEI film with fast Li+ transport kinetics. Notably, Li||Cu half cells exhibit an average CE reaching up to 99.56%. In particular, pouch cells equipped with high-loading lithium cobalt oxide (LCO, 3 mAh cm−2) cathodes, ultrathin Li chips (25 μm), and lean electrolytes (5 g Ah−1) demonstrate outstanding cycling performance, retaining 80% capacity after 125 cycles. To address the gas issue in the cathode under high voltage, cathode additives 1,3,6-tricyanohexane is incorporated with FGN-182; the resulting high-voltage LCO||Li (4.4 V) pouch cells can cycle steadily over 93 cycles. This study demonstrates that, even with the use of ether-based electrolytes, it is possible to simultaneously achieve significant improvements in both high Li utilization and electrolyte tolerance to high voltage by exploring appropriate functional additives for both the cathode and anode. Highlights: 1 FGN-182 electrolytes exhibit highly reversible Li plating/stripping with an average Coulombic efficiency reaching up to 99.56% determined from Auerbach’s test. 2 The gas-evolution process of LiNO3 in high-voltage lithium cobalt oxide (LCO) cathodes is revealed by in situ differential electrochemical mass spectrometry. 3 Pouch cells equipped with high-loading LCO (3 mAh cm−2) cathodes, ultrathin Li chips (25 μm), and lean electrolytes (5 g Ah−1) using optimized electrolyte (FGN-182 + 1%HTCN) demonstrate outstanding cycling performance.